Are children of rural migrants more delinquent than their peers?: a comparative analysis of delinquent behaviors in the City of Guangzhou, China - Liu, Jianhong (Crime, law and social change, 2016)
The social impact of rural-to-urban migration in China has grasped domestic and international attention over the past decades. Sociological scholarship indicates that this working class may be subject to social stigma and additional psychological stress. As new generations emerge, the migrant workers’ children are publicized to engage in higher level of delinquency and deviant behavior in large Chinese cities. However, this understanding is supported by little empirical evidence as few studies focus on the delinquent behaviors of rural migrant children compared to their urban counterparts. The current study explores this comparison using a high school student survey (N = 1,490) conducted in Guangzhou, Guangdong Province. Important contributing factors to the prevalence and variety of self-report delinquency are discussed in the multi-theory framework. Findings suggest that this sample of rural migrant students are exposed to more risks but are not more delinquency-prone than non-migrant students; results show support to quite different socialization processes for the two groups: strong moral beliefs and good academic performance play key roles in the prevention of delinquency for rural migrant students while non-rural migrants are affected by school attachment and negative social activities. Peer delinquency is the strongest predictor of delinquency for both groups.